Institutional health promotion standards in school of medicine at Shahid Beheshti University of Medical Sciences according to medical students’ opinions in 2020 - Aghababaie-babaki , Paria; Abachizadeh, Kambiz; Abdi, Saeed; Shekarriz-Foumani , Reza; Mohseni, Maryam (Social Determinants of Health, 2021)
Background: Health promotion in occupational and educational environments contributes to the improvement and higher efficiency of the people affected by them. The health status of medical students as future providers of health services has great importance. This study aimed to evaluate health promotion standards in the school of medicine at Shahid Beheshti University of Medical Sciences. Methods: This cross-sectional study evaluated health promotion standards of school of medicine using a questionnaire filled out by medical students in 2020. The validity and reliability of the questionnaire were confirmed. The questionnaire measured health promotion standards in the fields of healthy nutrition, facilities for proper physical activity, providing a healthy environment for students, adequate education for health promotion and disease prevention. Analytical and statistical tests were performed using IBM SPSS 23 software. Results: Among 340 medical students participated in the study 31.8 percent were in the basic sciences grade, 26.5 percent were stagers, and 41.8 percent were interns. The mean score of all questions among different grades was 1.11 (SD=0.33), 0.97 (SD=0.43), and 0.93 (SD=0.34), respectively (on a scale of 0-3). A significant difference was reported in the comparison of "basic sciences versus stagers (PV=0.011)" and "basic sciences versus interns (PV<0.01) ". the mean score of questions overall was 1.00 (SD=0.37). Conclusion: Based on findings, health promotion in the school of medicine at Shahid Beheshti University of Medical Sciences was in the medium range, which demonstrates the need for future policies that lead to a more efficient health-promoting environment.